Effect of C677T Mutation in Methiylenetetrahydrofolate Reductase Gene and Blood Folate on Hypertension Risk - Mohammad Hakimi, Abdul Salam M Sofro, Sunarti Ahmad Husain Asdie (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2007)
Background: The prevalence of hypertension risk factor varies among race or ethnic groups. The varied prevalence is associated with culture or genetic differences or interaction between genetic and environment or nutrition factorsObjective: The aim of this study was to identify relationship between polymorphism of C677T in MTHFR gene and folate status towards the risk of hypertension among Javanese population.Methods: This study was case-control nested, in